THE EFFECT OF ADDING Alpina galanga EXTRACT TO THE QUALITY OF FRESH MEAT Pangasius pangasiusDURING COLD STORAGE - Dwi Wendra; Suparmi Suparmi; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
AbstractPangasius pangasius is a type of fish that is very popular with the public and has economic value. Fish meat is easy to decline in quality and needs safe handling to maintain its quality, one of which is with galangal extract. Galangal extract contains antibacterial compounds that can prolong the decay process which will be stored at cold temperatures. The purpose of the study was to determine the effect of galangal juice on the freshness level of fish. The experimental research method consisted of two stages, 1) making galangal extract, 2). Soaking fish meat with galangal juice. The design of this study was a non-factorial randomized block design consisting of four levels of treatment, namely N0 (0% galangal extract from fish weight), N1 (15% galangal extract from fish weight), N2 (30% galangal extract from fish weight), N3 (45% by weight of fish ginger juice) with each storage time is 0, 1, 3, and 5 days at a cold temperature (± 2°C). The test results obtained the best treatment, namely N1 wasable to inhibit the deterioration of the quality of catfish meat with an odor value (4.32) criteria for non-fishy odor, galangal flavored, and fresh odor criteria. Texture value (4.38) with the criteria of a slightly dry texture, a little soft, and still fit for consumption. Then the value of the highest proximate the treatment of N3 levels of protein, fat content, water content in succession is; (10.62%), (1.48%), and (72.79%). Meanwhile, the TVB value of 11 mg/N is still safe for consumption. The pH value of 6.24 and the TPC value of 2.7x103colonies/gram were still below the threshold of SNI 01-2729.2-2006 so that during 5 days of storage it was still suitable for consumption.Keywords: Catfish, Cold temperature, Extract galangal